Quitosana e óleos essenciais em micropartículas: estratégias de controle para Histoplasma capsulatum e avaliação de patogenicidade em Caenorhabditis elegans - Costa, Anderson da Cunha (2025)
Histoplasma capsulatum, the causative agent of histoplasmosis, is a dimorphic fungus responsible for this infection. In addition to the limited pharmacological arsenal available for treating histoplasmosis, the fungus exhibits biofilm formation, a feature typically associated with increased antifungal tolerance. Therefore, chitosan and essential oils from lemongrass and geranium, encapsulated in chitosan microparticles and previously described for their antifungal activity, emerge as promising antifungal molecules against H. capsulatum. This study evaluated the effects of low-molecular-weight chitosan and essential oils encapsulated in microparticles on the planktonic form of the fungus, as well as the pharmacological interactions of these compounds with amphotericin B and itraconazole. Additionally, the impact of these molecules on H. capsulatum biofilms was analyzed. The virulence of H. capsulatum isolates was further investigated using Caenorhabditis elegans as a model organism. Twenty strains of H. capsulatum were included in this study. Antifungal activity against the planktonic form was assessed using broth microdilution assays, following CLSI protocols. Pharmacological interactions with amphotericin B and itraconazole were evaluated using the checkerboard technique. The effects of the molecules on biofilms were examined by quantifying biomass and metabolic activity through crystal violet staining and the MTT reduction assay, alongside microscopy techniques to analyze biofilm morphology. Strain pathogenicity was studied using the C. elegans model. Chitosan exhibited minimum inhibitory concentrations (MIC) ranging from 8 to 128 μg/mL, whereas microparticles displayed MIC values of 8 to 64 μg/mL against both the filamentous and yeast forms of H. capsulatum. Pharmacological interaction assays revealed synergism between both chitosan and microparticles with amphotericin B and itraconazole. Furthermore, these molecules reduced biofilm biomass and metabolic activity by up to 60%. Pathogenicity evaluation indicated that H. capsulatum caused 95% mortality in C. elegans. These findings underscore that chitosan and essential oils encapsulated in chitosan microparticles possess antifungal effects against both planktonic forms and biofilms of H. capsulatum, particularly demonstrating synergism with classical antifungal agents. Additionally, H. capsulatum yeast forms induced mortality in C. elegans, confirming their in vivo pathogenicity.